Street prostitution: Law enforcement and alternative responses. - Welsh, Brandon. (University of Ottawa (Canada), 1995)
This study examines law enforcement and alternative responses to street prostitution in those areas where street prostitution has been found to be most problematic: inner-city residential communities. Although not regarded as a serious concern to the majority of Canadians, street prostitution's impact and associated problems are shown to be of serious concern to this population. Traditional police suppression measures have demonstrated few gains in curbing street prostitution activities. A failure to employ other models of dealing with street prostitution--community re-design and social development--are found to be serious impediments to current policing policy. Limitations are as well noted by the police not engaging valuable community resources and expertise. To overcome these barriers this study proposes a multi-agency approach; bringing together police, residents' groups, and other key agencies in a systematic framework for the delivery of proactive interventions. A review of the literature on multi-agency approaches to address street prostitution reveals a few successes internationally. Findings of an examination of the response to street prostitution in the cities of Calgary and Edmonton reveal traces of success (and potential for) in the use of a multi-agency approach. Questions over the applicability of demonstrated successes to other settings and weak and sparse evaluation work of the initiatives in Calgary and Edmonton are sure to present significant barriers to any advancement of this approach. Recommendations are presented for a number of policy and academic directions to test these hurdles.
Keywords: Law.